2014
DOI: 10.16952/pns.2014.11.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review of Structural Equation Models for Hospital Nurses' Turnover Intention in Korea

Abstract: Purpose:The purpose of this study was to review research papers on structural equation models for hospital nurses' turnover intentions, and to identify the factors that influence these intentions. Methods: Twenty-four research papers on structural equation models for hospital nurses' turnover intentions were identified for systematic review. Results: All 24 papers assessed nurses' turnover intentions in general hospitals and university hospitals. A total of 36 indicators and 105 items were used to measure turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 28 publications
(10 reference statements)
4
15
1
Order By: Relevance
“…In the model, job stress had the largest direct effect on nurses' turnover intention; additionally, its indirect effect through burnout was significant. This result is consistent with prior studies' results . Burnout had the second‐largest effect on nurses' turnover intention; again, this is consistent with the results of prior studies …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the model, job stress had the largest direct effect on nurses' turnover intention; additionally, its indirect effect through burnout was significant. This result is consistent with prior studies' results . Burnout had the second‐largest effect on nurses' turnover intention; again, this is consistent with the results of prior studies …”
Section: Discussionsupporting
confidence: 92%
“…Emotional labour significantly indirectly affected turnover intention through job stress and burnout; however, its direct effect on turnover intention was not significant. These results are consistent with a previous study, which found that emotional labour indirectly affects turnover intention through job stress . As emotional labour's effect on turnover intention was mediated by job stress and burnout, nurse support programmes should aim to reduce nurses' emotional labour in order to effectively reduce nurses' turnover intention; further, interventions that address nurses' job stress and burnout might diminish nurses' turnover intention.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although many studies have investigated the factors influencing turnover intention of nurses (Jeong et al . , Kim & Kim , ), few studies have dealt with the effects of violence experienced by nurses on quality of life and turnover intention.…”
Section: Introductionmentioning
confidence: 99%